Time trends of genetic parameters in a White Leghorn population subjected to long term single trait selection - CHATTERJEE, R N; MISRA, B S; SINGH, H N (The Indian Journal of Animal Sciences, 2014)
A total of 2 263 pullets of 127 sires and 1 046 dams of 7 consecutive generations were studied. Females on the basis of their first 100 days egg production (EP 100) and cocks, on the basis of their sire family averages for EP 100 were selected every generation. The average correlated phenotypic response of age at sexual maturity (ASM) was negatively significant and of egg mass (EM), was positively significant. The average direct (of EP 100) and correlated (other than EP 100) phenotypic responses of the remaining traits were not significant. The pooled heritability estimates of ASM, WAM (weight at sexual maturity), EPlOoand EM were low to moderate while, for CS (clutch size), it was very low. The time trends of heritability estimates of WAM, EP 100' CS and EM were all negative except for ASM, which was positive. This study indicated that additive genetic variance of primary trait (EP 100) was reduced due to selection. The pooled estimates of genetic, environmental and phenotypic correlation of ASM with EP 100 CS and EM were all negative but between ASM and WAM, the estimate was positive. The estimates of correlation of WAM with other traits were small in magnitude (though significant) and inconsistent in direction. The pooled estimates of genetic, environmental and phenotypic correlation of EP 100 with CS and EM and between CS and EM were all highly (P